Progressive & religious how Christian, Jewish, Muslim, and Buddhist leaders are moving beyond the culture wars and transforming American life - Jones, Robert P. (Robert Patrick) (Lanham, Md. : Rowman & Littlefield Publishers : Distributed by National Book Network, 2008)
This volume tells the story of the emerging progressive religious movement (an exclusive claim on faith and values from the right and a radical divorce of faith from politics on the left) in America through an analysis of over 80 in-depth interviews with contemporary religious leaders including nationally known figures such as Rabbis David Saperstein and Michael Lerner, Revs. Jim Wallis and Brian McLaren, Feisal Abdul Rauf, Eboo Patel, Kecia Ali, Lama Surya Das, Robert Thurman, and E. J. Dionne. The author explains how progressive religious leaders are tapping the deep connections between religion and social justice to work on issues like poverty and workers' rights, the environment, health care, pluralism, and human rights.
Introduction: Moving beyond the culture wars : finding progressive religion in America -- Lifting the line of history : how progressive Jews are healing the world -- More truth breaking out : how progressive Christians are seeking the reign of God on earth -- Knowing one another : how progressive Muslims are fostering justice, beauty, and pluralism -- Just sitting down : how progressive Buddhists are being peace and embodying justice -- Conclusion: Progressive & religious : the new face of religion in American public life.
Includes bibliographical references (p. 237-248) and index.
Description based on print version record.
Keywords: United States -- Religion; Religion and culture -- United States; RELIGION / Sexuality & Gender Studies; Electronic books